Clinical Research - Rhythm, Indonesian Heart (Indonesian Journal of Cardiology, 2018)
Abstracts of the 6th Annual Scientific Meeting of the Indonesian Heart Rhythm Society Jakarta, 21-22 September 2018 Original Articles